IgG Anti-high-Density Lipoproteins Antibodies Discriminate Between Arterial and Venous Events in Thrombotic Antiphospholipid Syndrome Patients - Sciascia, Savino; Cecchi, Irene; Radin, Massimo; Rubini, Elena; Suárez, Ana; Roccatello, Dario; Rodríguez-Carrio, Javier (Frontiers in Medicine, 2019)
Introduction: Recurrent thrombotic events are a hallmark of Antiphospholipid Syndrome (APS). However, biomarkers to identify if a patient with antiphospholipid antibodies (aPL) is at higher risk to develop an arterial or a venous event are lacking. Recently, the pathogenic role of anti-high-density lipoproteins antibodies (anti-HDL) in the occurrence of cardiovascular disease in autoimmunity has emerged. The aim of the present study was to evaluate the presence of IgG anti-HDL antibodies in a cohort of thrombotic APS patients and to investigate their association with clinical outcomes. Methods: Serum levels of IgG anti-HDL antibodies, total IgG and complete aPL profile were assessed in 60 APS patients and 80 healthy donors (HDs) by immunoassays. Results: Higher levels of IgG anti-HDL were found in APS patients compared to HDs (p<0.001), even after correcting for total IgG levels (p<0.001). No associations with treatments or traditional cardiovascular risk factors, except for smoking habit (p<0.0001), were found. Patients who experienced at least one arterial event (n=30) had significantly higher levels of anti-HDL antibodies when compared to patients with venous thrombosis (n=30, p=0.046), this difference being stronger when adjusting for total IgG (p=0.007). Additionally, patients tested positive for antiphosphatidylserine/prothrombin (IgG/IgM) antibodies had significantly higher levels of anti-HDL antibodies (p=0.045). Conclusions: Increased levels of IgG anti-HDL antibodies can be found in APS, mainly in patients with arterial thrombosis, independently of aPL antibodies and traditional risk factors. These findings point to a role of anti-HDL antibodies in APS and support their use as a potential biomarker for arterial thrombotic events.